2016
DOI: 10.1038/nature18600
|View full text |Cite
|
Sign up to set email alerts
|

A combinatorial strategy for treating KRAS-mutant lung cancer

Abstract: Therapeutic targeting of KRAS-mutant lung adenocarcinoma represents a major goal of clinical oncology. KRAS itself has proven difficult to inhibit, and the effectiveness of agents that target key KRAS effectors has been thwarted by activation of compensatory or parallel pathways that limit their efficacy as single agents. Here we take a systematic approach towards identifying combination targets for trametinib, an FDA-approved MEK inhibitor that acts downstream of KRAS to suppress signaling through the mitogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
330
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(355 citation statements)
references
References 36 publications
22
330
0
Order By: Relevance
“…TRA was shown to affect the fibroblast growth factor receptor 1 (FGFR1) leading to drug resistance [32]. In a recent study, inhibition of FGFR1 in combination with TRA enhanced cancer cell death in vitro and in vivo [32].…”
Section: Resultsmentioning
confidence: 99%
“…TRA was shown to affect the fibroblast growth factor receptor 1 (FGFR1) leading to drug resistance [32]. In a recent study, inhibition of FGFR1 in combination with TRA enhanced cancer cell death in vitro and in vivo [32].…”
Section: Resultsmentioning
confidence: 99%
“…These studies have also shown that KRAS mutant cells harbor increased dependence on RTK signaling pathways, as small molecule inhibitors of IGF1R and MET exhibit some preferential selectivity for subsets of KRAS mutant lines over KRAS wild-type lines (Ebi et al 2011; Molina-Arcas et al 2013). In addition, MAPK inhibition leads to increased dependence on RTK signaling, with combined targeting of MEK1/2 and IGF1R (Ebi et al 2011; Molina-Arcas et al 2013) or FGFR1 (Manchado et al 2016) demonstrating enhanced differential impact on KRAS mutant cells over wild-type cells. Moreover, KRAS-MAPK effector signaling ultimately leads to activation of AP-1 transcription factors and upregulation of cell cycle regulatory proteins, such as cyclin D1 ( CCND1 ) which promotes G1/S cell cycle progression.…”
Section: Inhibiting Kras Effector Pathways In Kras Mutant Cancersmentioning
confidence: 99%
“…Lastly, since most treatment strategies in KRAS mutant cancers will require combination therapies, functional genetic screening in the context of small molecule inhibition of key KRAS effector signaling pathways may prove most fruitful for the identification of high-priority KRAS synthetic lethal interactions. A number of screens have been performed using RNAi technologies to identify combination therapy targets with MAPK pathway inhibition, including FGFR1 (Manchado et al 2016), BCL-XL (Corcoran et al 2013), YAP1 (Lin et al 2015) and PTPN11 (Prahallad et al 2015). …”
Section: Next Steps In Discovery and Utilization Of Kras Synthetic Lementioning
confidence: 99%
“…For instance, treating metastatic melanomas harboring the common BRAF(V600E) mutation with a small-molecule inhibitor leads to tumor regression followed by recurrence of tumors capable of bypassing BRAF to activate downstream mitogenic MAPK signaling, but importantly these future science group Review Adler, Mittal, Ryan, Zhou, Wasser & Vella variant tumors can be responsive to cotreatment with an MEK inhibitor [4]. Similarly, KRAS-mutant lung tumors develop resistance to MEK inhibition via compensatory mitogenic signals received through FGFR1 and thus become susceptible to FGFR1 inhibition [97]. Given the reciprocal effects, checkpoint inhibitors and costimulatory agonists have in regulating T-cell responsiveness by relieving negative and potentiating positive signals, respectively, it was perhaps logical that combining biologics from each class do enhance therapeutic efficacy [82][83][84].…”
Section: Immunotherapies Overcome Tumor-induced Immunosuppressionmentioning
confidence: 99%